Persistence of Antibodies to 2 Virus-Like Particle Norovirus Vaccine Candidate Formulations in Healthy Adults: 1-Year Follow-up With Memory Probe Vaccination. (19th April 2019) - Atmar, Robert L; Baehner, Frank; Cramer, Jakob P; Lloyd, Eric; Sherwood, James; Borkowski, Astrid; Mendelman, Paul M; ,
Abstract: Background: We previously reported the tolerability and immunogenicity 1 month after intramuscular administration of 2 bivalent virus-like particle (VLP)–based candidate norovirus vaccine formulations in adults. We now describe the persistence of immunity and responses to a memory probe vaccination 1 year later. Methods: A total of 454 healthy men and women aged 18–49 years in 3 equal groups received placebo (saline) or 15/50 or 50/50 vaccine formulations (ie, 15 or 50 µg of GI.1 genotype VLPs, respectively, and 50 µg of GII.4c VLPs) with MPL and Al(OH)3 . Immunogenicity and safety were assessed up to day 365, when 351 participants received a memory probe vaccination of 15 µg each of GI.1 and GII.4c VLPs with Al(OH)3 . Results: No safety signals were detected up to 1 year after the first vaccination. Pan-immunoglobulin, immunoglobulin A, and histo-blood group antigen–blocking (HBGA) antibody levels among vaccinees waned but remained higher than levels before vaccination and levels in placebo recipients on days 180 and 365. Memory probe vaccination increased all antibody titers. Levels of HBGA antibodies to GI.1 but not GII.4c were higher after the first vaccination in candidate vaccine groups, compared with those in the placebo group. Conclusion: Levels of antibodies to both candidate norovirus VLP formulations persisted above baseline levels for at least 1 year after primary vaccination. HBGA-blocking responses to the memory probe for GI.1 but not GII.4c displayed characteristics of immune memory. Clinical Trials Registration: NCT02142504. Abstract : Serum antibody levels remained above baseline levels for 1 year after initial administration of a bivalent virus-like particle–based norovirus vaccine and were boosted when a memory probe vaccine dose was administered approximately 1 year after the first vaccination.